Potentiation effects of the French contrast method on vertical jumping ability - Hernandez-Preciado, J. A.; Baz, E.; Balsalobre-Fernandez, C.; Marchante, D.; Santos-Concejero, J. (The Journal of Strength and Conditioning Research, 2019)
This study examined the acute effects of the potentiation protocol known as French Contrast Method on the vertical jumping ability measured using a countermovement jump (CMJ). Thirty-one athletes participated in this study (intervention group n = 17 and control group n = 14). The CMJ height was measured using the iOS application My Jump 2.0 before and after the French Contrast protocol, which consisted of 3 sets of isometric partial squats, drop jumps, dynamic half-squats, and hurdle jumps. The CMJ height improved from its baseline values by 5.1 ± 1.1% (p < 0.001, effect size [ES] = 0.27) after the first set, by 6.8 ± 1.8% (p < 0.001, ES = 0.41) after the second set, and by 8.5 ± 2.9% (p < 0.001, ES = 0.44) after the third set. The maximal potentiation value was an increase of 11 ± 6.3% (p < 0.001). The control group decreased its CMJ height from the baseline levels, reaching a significant decrement of -2.1 ± 1.6% (p = 0.047). These findings suggest that the French Contrast Method is a valid strategy to improve the vertical jumping ability. This method can be used after the warm-up as a conditioning activity to acutely enhance the lower body's force and power production.